2022
DOI: 10.3389/fpls.2022.988352
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive phytochemical, biological, and toxicological studies of roots and aerial parts of Crotalaria burhia Buch.-Ham: An important medicinal plant

Abstract: This study was designed to seek the phytochemical analysis, antioxidant, enzyme inhibition, and toxicity potentials of methanol and dichloromethane (DCM) extracts of aerial and root parts of Crotalaria burhia. Total bioactive content, high-performance liquid chromatography-photodiode array detector (HPLC-PDA) polyphenolic quantification, and ultra-high performance liquid chromatography-mass spectrometry (UHPLC-MS) analysis were utilized to evaluate the phytochemical composition. Antioxidant [including 2,2-diph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…Orchidaceae tubers [194] Anacardium occidentale Anacardiaceae leaves [195] Anacardium occidentale Anacardiaceae fruits [196] Andropogon virginicus Poaceae aerial parts [197] Angelica keiskei Umbelliferae leaves, roots [198] Arachis hypogaea Fabaceae peanut shell [154] Areca catechu Palmaceae fruits [195] Arctium minus Asteraceae flower heads, leaves, roots [199] Artemisia verlotiorum Asteraceae whole plant [200] Atractylodis macrocephalae Asteraceae rhizomes [201] Berberis thunbergii Berberidaceae leaves [202] Bergenia pacumbis Saxifragaceae plant and its rhizomes [203] Blepharis linariifolia Acanthaceae aerial parts [204] Bletilla striata Orchidaceae tubers, fibrous roots [205] Breynia retusa Phyllanthaceae leaves [206] Bridelia ferruginea Phyllanthaceae leaves, stem bark [207] Bruguiera gymnorhiza Rhizophoraceae leaves, roots, fruits [158] Cakile maritima Brassicaceae fruits, leaves, stems [208] Cannabis sativa Cannabaceae seeds [169] Carthamus tinctorius Asteraceae seeds [209] Celastrus hindsii Celastracea leaves [210] Cercis glabra Fabaceae leaves [211] Cladium mariscus Cyperaceae seeds [212] Clausena indica Rutaceae roots [213] Combretum micranthum Combretaceae leaves [196] Crotalaria burhia Fabaceae aerial parts, roots [214] Croton hirtus Euphorbiaceae aerial parts [215] Cudrania tricuspidata Moraceae fruits [216] Cytinus hypocistis Cytinaceae aerial parts [217] Dianella ensifolia Liliaceae roots [218] Dodonaea viscosa Sapindaceae stems [219] Elaeagnus angustifolia Elaeagnaceae fruits, leaves [220] Table 4. Cont.…”
Section: Anacamptis Pyramidalismentioning
confidence: 99%
“…Orchidaceae tubers [194] Anacardium occidentale Anacardiaceae leaves [195] Anacardium occidentale Anacardiaceae fruits [196] Andropogon virginicus Poaceae aerial parts [197] Angelica keiskei Umbelliferae leaves, roots [198] Arachis hypogaea Fabaceae peanut shell [154] Areca catechu Palmaceae fruits [195] Arctium minus Asteraceae flower heads, leaves, roots [199] Artemisia verlotiorum Asteraceae whole plant [200] Atractylodis macrocephalae Asteraceae rhizomes [201] Berberis thunbergii Berberidaceae leaves [202] Bergenia pacumbis Saxifragaceae plant and its rhizomes [203] Blepharis linariifolia Acanthaceae aerial parts [204] Bletilla striata Orchidaceae tubers, fibrous roots [205] Breynia retusa Phyllanthaceae leaves [206] Bridelia ferruginea Phyllanthaceae leaves, stem bark [207] Bruguiera gymnorhiza Rhizophoraceae leaves, roots, fruits [158] Cakile maritima Brassicaceae fruits, leaves, stems [208] Cannabis sativa Cannabaceae seeds [169] Carthamus tinctorius Asteraceae seeds [209] Celastrus hindsii Celastracea leaves [210] Cercis glabra Fabaceae leaves [211] Cladium mariscus Cyperaceae seeds [212] Clausena indica Rutaceae roots [213] Combretum micranthum Combretaceae leaves [196] Crotalaria burhia Fabaceae aerial parts, roots [214] Croton hirtus Euphorbiaceae aerial parts [215] Cudrania tricuspidata Moraceae fruits [216] Cytinus hypocistis Cytinaceae aerial parts [217] Dianella ensifolia Liliaceae roots [218] Dodonaea viscosa Sapindaceae stems [219] Elaeagnus angustifolia Elaeagnaceae fruits, leaves [220] Table 4. Cont.…”
Section: Anacamptis Pyramidalismentioning
confidence: 99%
“…Due to C. longirostrata being a poorly studied plant, there is limited information available regarding studies on its enzymatic inhibition. However, a comparison was made with research conducted by Anwar et al in 2022 [59], where a plant called Crotalaria burhia Buch.-Ham, belonging to the same genus as C. longirostrata, was studied. In this study, the inhibitory activity of α-Amylase was measured, and it was found that with methanol extracts, an IC 50 inhibition of 0.63 mmol/g was observed.…”
Section: α-Amylase Inhibitionmentioning
confidence: 99%